2014
DOI: 10.1155/2014/906021
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning Carbon Dioxide Emission and Assessing Dissolved Organic Carbon Leaching of a Drained Peatland Cultivated with Pineapple at Saratok, Malaysia

Abstract: Pineapples (Ananas comosus (L.) Merr.) cultivation on drained peats could affect the release of carbon dioxide (CO2) into the atmosphere and also the leaching of dissolved organic carbon (DOC). Carbon dioxide emission needs to be partitioned before deciding on whether cultivated peat is net sink or net source of carbon. Partitioning of CO2 emission into root respiration, microbial respiration, and oxidative peat decomposition was achieved using a lysimeter experiment with three treatments: peat soil cultivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
4
2
Order By: Relevance
“…Total nitrogen, exchangeable ammonium, and available nitrate decreased with increasing depth because of decrease in the peat oxidation (with increasing water content). Ammonium and nitrate contents of the peat soil were higher than the reported range (Sim et al 2012;Choo and Ahmed 2014) because this present study was carried out on a cultivated sapric peat whereas that reported by Sim et al 2012…”
Section: Peat Soil Propertiescontrasting
confidence: 65%
See 2 more Smart Citations
“…Total nitrogen, exchangeable ammonium, and available nitrate decreased with increasing depth because of decrease in the peat oxidation (with increasing water content). Ammonium and nitrate contents of the peat soil were higher than the reported range (Sim et al 2012;Choo and Ahmed 2014) because this present study was carried out on a cultivated sapric peat whereas that reported by Sim et al 2012…”
Section: Peat Soil Propertiescontrasting
confidence: 65%
“…Bulk density and water holding capacity of the peat soil showed no significant difference with depth whereas soil moisture increased with increasing depth. Exchangeable ammonium and available nitrate results were higher than those in the literature (Choo and Ahmed 2014;Sim et al 2012).…”
Section: Peat Soil Physical and Chemical Propertiescontrasting
confidence: 56%
See 1 more Smart Citation
“…These may be related to microbiome feedback during macadamia plant growth in these substrates [ 40 ]. Tropical peat soils are generally defined as soils formed by the accumulation of partially decayed woody plant materials under waterlogged condition [ 41 ]. Perlite and wood bran are commonly used in fruit and vegetables growth substrates [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the oil palm industry, where extensive studies had been carried out to measure greenhouse gas emissions from oil palm plantations on peat [11][12][13], less attention has been focused on drained peatlands under pineapples cultivation. Pineapples cultivation on peat soils in Malaysia was reported to release approximately 179.6 t CO 2 ha −1 yr −1 [14] and 15.7 t N 2 O ha −1 yr −1 [15]. While efforts had been carried out to quantify CO 2 and N 2 O emissions from tropical peat soils cultivated with pineapple [16][17][18][19], the effects of pineapple residue ash on CO 2 and N 2 O emissions from drained peat soils are yet to be determined in field and laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%